Rhetoric and persuasion: understanding enthymemes in the public sphere - Faure, Murray (Acta Academica: Critical views on society, culture and politics, 2010)
The enthymeme has been used and analysed for over two millennia. It is one of the most powerful rhetorical instruments used for the purpose of persuasion, be it through the spoken or written word. This article explores the origins and complexities of the instrument and demonstrates its use and significance in the public sphere by analysing style and rhetorical content in the writings of St Paul, Dr Martin Luther King Jnr and President George W Bush. The conclusions suggest that further research into this rhetorical instrument could uncover a layer of understanding of political discourse in the public sphere hitherto not undertaken by local scholars.